Efektifitas POC Sabut Kelapa Dan Serbuk Cangkang Telur pada Produktifitas Lobak Putih (Raphanus sativus L) - Rahmad Pribadi; Nanik Lutfiyah; Mohammad Fatoni (Universitas Darul Ulum, 2022)
White bean is a potential vegetable crop and can be developed into a profitable commodity because of its high productivity. The purpose of this study was to determine the effect of coconut-based organic liquid fertilizer (OLF) and chicken eggshell-based flour on the growth of white radish (Raphanus sativus var. longipinnatus). This research was carried out via factorial Completely Randomized Design (CRD), which consisted of two factors and three replications. The first factor is the concentration of coconut-based OLF (S) consisting of: S0 = 0 /polybag, S1 = 150 /polybag, S2 = 300 /polybag, S3 = 450 /polybag, the second factor is chicken eggshell powder (C) consisting of: C0= 0 /polybag, C1= 12.5 /polybag, C2= 25 /polybag, C3= 37.5 /polybag. The data analysis technique implemented variance analysis and then tested the Least Significant Different (LSD) of 5%. The results showed that the administration of coconut-based OLF and chicken eggshell powder significantly affected the growth of white radish plants. In the combination treatment, the concentration of coconut-based OLF and chicken eggshell powder (S3C3) was 450 /polybag and 37.5 /polybag, respectively. It gave the best results on stover weight, tube weight and a tube diameter of white radish (Raphanus sativus var. longipinnatus).